Smart City Application: Android Based Smart Parking System - Kilic, Talha; Tuncer, Taner (Ieee, 2017)
Wireless sensor networks consist of many sensors designed to provide information flow from a specific area. Sensors communicate with each other and receive information from the environment. The information obtained from the physical environment is carried into the network environment. In recent years, improvements in wireless sensor networks have necessitated the control, observation, data collection and storage of large physical areas. Especially in crowded cities, it is compulsory to collect and process data on physical infrastructure, air pollution, traffic and many similar issues. Therefore, cities become smart environments. The smart city structure aims to combine data from different sources for different purposes under a single point. In this article, we provide a framework that can instantly communicate park information to customers in different parts of the city. For this, parking information is stored in a database using cloud architecture through the sensors in the parking lot entrances. Customers can obtain parking information stored in the database with an improved mobile application. With smart parking system, it is possible to find suitable parking place, to prevent loss of customers time and to reduce costs.
Akilli şehir uygulamasi: Android tabanli akilli otopark sistemi
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Motion Sensor; Smart Parking System; Cloud Computing; Windows Azure Platform